Chemical Shrinkage of Paste and Mortar Containing Limestone Fines - Khatib, Jamal M; Ramadan, Rawan; Ghanem, Hassan; Elkordi, Adel; Baalbaki, Oussama; Kırgız, Mehmet Serkan; Kırgız, Mehmet Serkan (Elsevier Ltd., 2022)
The effect of including limestone fine (LF) on the chemical shrinkage of cement paste and mortar is investigated. The cement was partially replaced with 0 to 20% (by weight) with LF. The water to cementitious material (CM) ratio was maintained at 0.45. In the mortar mixes, the proportion of sand (S) to CM was 1:2. In addition to the chemical shrinkage test, compressive strength and density of specimens were determined. The chemical shrinkage data were collected up to 28 days. However, for compressive strength and density, testing continued up to 90 days of water curing. There appears to be an increase in chemical shrinkage between 10 and 15% limestone for both paste and mortar mixes. The trend appears to be similar for the compressive and density results.
Keywords: Limestone fines; Chemical shrinkage; Density; Compressive strength; Paste Mortar